Quantitative genome-wide methylation analysis of high-grade non-muscle invasive bladder cancer - Kitchen, Mark O.; Bryan, Richard T.; Emes, Richard D.; Glossop, John R.; Luscombe, Christopher; Cheng, K.K.; Zeegers, Maurice P.; James, Nicholas D.; Devall, Adam J.; Mein, Charles A.; Gommersall, Lyndon; Fryer, Anthony A.; et al. (Taylor & Francis, 2016)
High-grade non-muscle invasive bladder cancer (HG-NMIBC) is a clinically unpredictable disease with greater risks of recurrence and progression relative to their low-intermediate-grade counterparts. The molecular events, including those affecting the epigenome, that characterise this disease entity in the context of tumour development, recurrence and progression, are incompletely understood. We therefore interrogated genome-wide DNA methylation using HumanMethylation450 BeadChip-arrays in 21 primary HG-NMIBC tumours relative to normal bladder controls. Using strict inclusion-exclusion criteria we identified 1,057 hypermethylated CpGs within gene promoter-associated CpG islands, representing 256 genes. Bisulphite Pyrosequencing validated the array data and examined 25 array-identified candidate genes in an independent cohort of 30 HG-NMIBC and 18 low-intermediate-grade NMIBC. These analyses revealed significantly higher methylation frequencies in high-grade tumours relative to low-intermediate-grade tumours for the ATP5G2, IRX1 and VAX2 genes (p<0.05), and similarly significant increases in mean levels of methylation in high-grade tumours for the ATP5G2, VAX2, INSRR, PRDM14, VSX1, TFAP2b, PRRX1, and HIST1H4F genes (p<0.05). Although inappropriate promoter methylation was not invariantly associated with reduced transcript expression, a significant association was apparent for the ARHGEF4, PON3, STAT5a, and VAX2 gene transcripts (p<0.05). Herein, we present the first genome-wide DNA methylation analysis in a unique HG-NMIBC cohort, showing extensive and discrete methylation changes relative to normal bladder and low-intermediate-grade tumours. The genes we identified hold significant potential as targets for novel therapeutic intervention either alone, or in combination, with more conventional therapeutic options in the treatment of this clinically unpredictable disease.